Eksplorasi Pengalaman Mahasiswa dalam Memahami Konsep Zakat sebagai Calon Muzakki - Valentina Monoarfa; Alisya Adam; Siti Rahmawati Pou; Rahmawati Djiki (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The purpose of this study was to explore students' understanding of zakat as prospective zakat payers. This study used a qualitative approach with a phenomenological method implemented through interviews with eight Muslim undergraduate students at Gorontalo State University, selected using a purposive sampling technique. Data were analyzed using the Miles and Huberman model. The research findings revealed that students understood zakat as a religious obligation and a form of concern for others. They were also familiar with various types of zakat, such as zakat fitrah and zakat mal, as well as the concepts of nisab and haul. However, their understanding was still basic and did not include technical aspects such as how to calculate zakat. Although most were not yet obligated to pay zakat mal, students demonstrated awareness and intention to fulfill this obligation in the future.